THE EVERYDAY LIFE OF WOMEN LIVING WITH HIV IN BANDUNG CITY - Putri, Maulina Thahara; Herawati, Erna; Harahap, Junardi (Sosiohumaniora, 2024)
The everyday lives of people living with HIV/AIDS are often filled with challenges stemming from physical, mental, and socio-cultural aspects. Among them, many are able to face these challenges, while some struggle to do so. Women living with HIV face even greater challenges due to their gender roles in society, whether as single women, mothers, wives, or daughters-in-law. This study describes the dynamic challenges faced by women living with HIV in Bandung City in their daily lives. These challenges go beyond biological aspects and include the ways they confront them. The research employs a phenomenological method, with data collected through in-depth interviews and participant observation involving women with HIV/AIDS who are either housewives or workers. The findings reveal that the everyday lives of women living with HIV/AIDS in Bandung are marked by issues related to their physical, mental, socio-cultural, and economic conditions. After being infected, their physical health often deteriorates, requiring them to adapt to these conditions to maintain their daily activities. They also experience mental pressure due to the need to hide their health status because of societal stigma. Some women fail to manage these challenges and experience stress, while others successfully cope with them. Remarkably, some women manage to empower themselves and live fulfilling lives.